STUDIES ON THE AGE DETERMINATION OF ’GHOL’, PSEUDOSCI^NA DIACANTHUS (LACEPEDE) BY MEANS OF SCALES AND OTOLITHS - Rao, K Venkatasubba (Indian Journal of Fisheries, 2011)
THE fact that tropical fishes also show periodical growth checks (rings) ontheir discrete hard parts has been demonstrated in a few Indian species (Nair,1949; Seshappa and Bhimachar, 1951, 1954, 1955; Pillai, 1954; Radhakrishnan,1954, 1957; Sarojini, 1957; Jhingran, 1957; Seshappa, 1958and Balan, 1959). Work on the biology and fishery of Pseudosciana diacanthusoccurring in the waters off Maharashtra and Gujarat coasts wasstarted by the present author in March, 1958 and during the course of twoyears study, it has been found that the scales and otohths of this speciesshow growth checks (rings) which can be utilised for the determination ofage and growth as was indicated by Seshappa (1953).